2019
DOI: 10.1093/mnras/stz3574
|View full text |Cite
|
Sign up to set email alerts
|

The performance of photometric reverberation mapping at high redshift and the reliability of damped random walk models

Abstract: Accurate methods for reverberation mapping using photometry are highly sought after since they are inherently less resource intensive than spectroscopic techniques. However, the effectiveness of photometric reverberation mapping for estimating black hole masses is sparsely investigated at redshifts higher than z ≈ 0.04. Furthermore, photometric methods frequently assume a Damped Random Walk (DRW) model, which may not be universally applicable. We perform photometric reverberation mapping using the Javelin phot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
(202 reference statements)
0
2
0
Order By: Relevance
“…Antonucci 1993;Lacy et al 2004;Martínez-Sansigre et al 2005), since accretion processes are variable (e.g. Read et al 2020) and since AGN are highly multimodal (e.g. Hardcastle et al 2007;Best & Heckman 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Antonucci 1993;Lacy et al 2004;Martínez-Sansigre et al 2005), since accretion processes are variable (e.g. Read et al 2020) and since AGN are highly multimodal (e.g. Hardcastle et al 2007;Best & Heckman 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to CREAM, JAVELIN (Zu et al 2011) uses a damped random walk (DRW) model to describe the stochastic variability of the quasar lightcurves. Even though the DRW model may be an incomplete description for quasars on short timescales (Mushotzky et al 2011;Kozłowski 2016), studies have shown that the DRW model still provides a flexible approach to accurately measuring lags (Li et al 2019;Read et al 2020) and a reasonable fit to observations of quasar variability on the timescales of our monitoring program (days to weeks) (Kelly et al 2009;MacLeod et al 2010MacLeod et al , 2012Kozłowski 2016).…”
Section: Lag Identificationmentioning
confidence: 99%